Effects of blended learning and peer tutoring on genetics achievement among agricultural education students in North Central Nigeria - Bolakale, Jimoh Saidu; Ojo, Afolabi Kayode; Bature, Shuaib Suleiman; Olorunleke, Adesanya Emmanuel (Indonesian Journal of Curriculum and Educational Technology Studies, 2024)
This study examined the effects of Blended Learning (BL) and Peer Tutoring (PT) on student achievement in genetics among agricultural education students in North Central Nigeria. Using a quasi-experimental design, 167 students from three education colleges were divided into experimental and control groups. The Genetics Achievement Test (GAT) and the Genetics Blended Learning Package (GBLP) assessed learning outcomes. Pre- and post-test results showed that students taught with BL and PT outperformed traditional methods, with BL being the most effective. Gender differences were also observed, with male students performing better across all methods. The study concludes that both BL and PT enhance learning and recommend their adoption. Additionally, schools should integrate innovative teaching methods and ICT tools to improve instruction in complex subjects.